The Alchemical Factor in Early Cookery - Erevnídis, Pávlos (Petits Propos Culinaires, 2006)
The author complains about conceptual confusion evident in the use of the term alchemy when referring to culinary skills and goes on to explore whether the texts of some Greek alchemists of late antiquity can provide insights into past cooking techniques.